Diagnosing sarcoidosis. Issue 5 (September 2015) - Culver, Daniel A.
Abstract : Purpose of review: The usual diagnostic criteria for sarcoidosis include the documentation of a compatible clinicoradiologic scenario, biopsy proof of granulomas, and exclusion of alternate causes for the findings. Establishing the presence of multisystem disease, and longitudinal assessment for the emergence of potential sarcoidosis mimics both strengthen the diagnosis. These principles have constituted a ' diagnostic modus operandi ' for several decades, but the emergence of several new technologies has begun to transform their application. Recent findings: The widespread availability of high-resolution chest computed tomography, endobronchial ultrasound-guided transbronchial needle aspiration, rapid on-site cytopathology and to a lesser degree, fluorodeoxyglucose positron emission tomography have facilitated more convenient diagnosis. They also have identified possibilities for biopsy-less diagnosis in appropriate clinical contexts, similar to idiopathic pulmonary fibrosis, and allowed for more comprehensive assessment of the extent and activity of disease. Nonetheless, these new technologies cannot replace the central role of the clinician, whose judgment and circumspection are keys to accurate diagnosis. Summary: The diagnosis of sarcoidosis and the assessment of its extent should be tailored to the clinical situation. The application of new technologies may permit some evolution of the diagnostic approach in many patients.